2009 International Conference on Intelligent Sensors, Sensor Networks and Information Processing (ISSNIP) 2009
DOI: 10.1109/issnip.2009.5416743
|View full text |Cite
|
Sign up to set email alerts
|

TinyIBE: Identity-based encryption for heterogeneous sensor networks

Abstract: Abstract-The area of security for Heterogeneous Sensor Networks (HSNs) is still an open research field that requires new cryptographic solutions. Recent results have demonstrated that Elliptic Curve Cryptography (ECC) and Pairing-Based Cryptography (PBC) are computationally feasible on sensor devices. This allows a wide range of novel security mechanisms, like IdentityBased Encryption (IBE), to be considered for Wireless Sensor Networks (WSNs).In this paper we present an efficient security bootstrapping mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…i ≠ H2'(e'(T, C1)) ⊕ C2 (5) Moreover in the opposite way, the adversary is not able to correctly calculate the session key j generated by the legitimate RFID tag, since: j ≠ H2'(e'( , C3)) ⊕ C4 (6) Thus, an adversary is not able to access the information both from the legitimate RFID reader and legitimate RFID tag.…”
Section: Msmentioning
confidence: 99%
“…i ≠ H2'(e'(T, C1)) ⊕ C2 (5) Moreover in the opposite way, the adversary is not able to correctly calculate the session key j generated by the legitimate RFID tag, since: j ≠ H2'(e'( , C3)) ⊕ C4 (6) Thus, an adversary is not able to access the information both from the legitimate RFID reader and legitimate RFID tag.…”
Section: Msmentioning
confidence: 99%
“…In the context of IBE for WSN, Szczechowiak and Collier [4] proposed TinyIBE using ƞT pairing to disprove the argument that using IBE is too heavy for sensor node. They demonstrated that it is feasible to enforce the ƞT pairing even on at very constrained nodes.…”
Section: Related Workmentioning
confidence: 99%
“… Light-weight cryptographic operation with highlevel security strength: IMAKA-Tate uses 128 bit security strength of ƞT paring. This method is known as the most light-weight cryptographic operation, even it is feasible for the most constrained sensor node [4]. In addition, such security strength is about same as the 3072 bit of RSA method.…”
Section: Security Featuresmentioning
confidence: 99%
“…The key pre-distribution scheme proposed by Eschenauer and Gligor [9], Du et.al [10,11], and TinyIBE [12] is used for comparison. Although the WSN architecture presented above is between sensor node and base station only, our scheme is flexible to be implemented in hierarchal structure that may consist of base station, sensor node and cluster head.…”
Section: Proposed Ibe-trust Security Frameworkmentioning
confidence: 99%